The tiger who came to tea - Kerr, Judith; Wood, David (Harpercollins Childs UK, 2006)
"The Tiger Who Came to Tea" is a charming tale about a tiger who unexpectedly visits a little girl$1 (Bs home and eats all the food. The story is playful and imaginative, highlighting the fun of unexpected surprises and the importance of sharing.s